Vertically Transmitted Gut Bacteria and Nutrition Influence the Immunity and Fitness of Bactrocera dorsalis Larvae - Hassan, Babar; Siddiqui, Junaid Ali; Xu, Yijuan (Frontiers in Microbiology, 2020)
Symbiotic bacterial communities that colonize the digestive tract of tephritid fruit flies interact with nutrient intake to improve the flies’ fitness and immunity. Some bacterial species consistently inhabit the tephritid guts and are transmitted to the next generation vertically. These species contribute significantly to some aspects of their host's physiology. In the current study, we examined the role of four vertically transmitted bacteria (Citrobacter, Enterobacter, Klebsiella, and Providencia) on the fitness parameters and immunity of B. dorsalis larvae that were fed a nutritionally manipulated diet. For this purpose, eggs were collected from axenic, gnotobiotic, and symbiotic adult flies, and larvae were reared on four types of diets in which carbohydrate and/or protein contents were reduced and then compared with larvae raised on a control diet. The diet and bacterial interactions significantly affected the fitness and immunity of B. dorsalis. Larvae of axenic flies grew slower and displayed weaker immune-based responses (PO activity, antibacterial activity, survival) than larvae of gnotobiotic and symbiotic flies. Overall, larvae reared on the low-protein diet grew slower than those reared on the control or low-carbohydrate diets. Survival, PO activity, and antibacterial activity were significantly lower in the hemolymph of larvae reared on low-protein diets. Our results also revealed that the levels of hemolymph protein, glucose, trehalose, and triglyceride in larvae from axenic flies were significantly lower than those in larvae of the symbiotic group after they fed on most of the tested diets. These results strongly infer that diet and vertically transmitted bacteria are both essential contributors to the fitness and immunity of B. dorsalis.